ICPEP INTEGRATES PHARMACY EDUCATION AND PRACTICE TO IMPROVE HEALTHCARE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, February 2016 Pharmacy academicians and researchers in tertiary institutions need to work more closely with pharmacy service providers and practitioners to further improve the healthcare system of the country.